2015
DOI: 10.1200/jop.2014.002428
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Discontinuing Chemotherapy for Metastatic Non–Small-Cell Lung Cancer at the End of Life

Abstract: Purpose: Administration of chemotherapy close to death is widely recognized as poor-quality care. Prior research has focused on predictors and outcomes of chemotherapy administration at the end of life. This study describes processes of chemotherapy discontinuation and examines their relationships with timing before death, hospice referral, and hospital death. Patients and Methods:We reviewed health records of a prospective cohort of 151 patients with newly diagnosed metastatic nonsmall-cell lung cancer who pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Administration of chemotherapy close to death usually represents poorly planned care. 28 It was encouraging to find that only 5% of our study population received chemotherapy within the last 4 weeks of life, however, this limited the potential to explore the impact of palliative care on late chemotherapy. Studies that have established an association between palliative care team involvement and lower rates of chemotherapy near the end of life have concluded that cessation of chemotherapy is due to palliative care involvement.…”
Section: Discussionmentioning
confidence: 93%
“…Administration of chemotherapy close to death usually represents poorly planned care. 28 It was encouraging to find that only 5% of our study population received chemotherapy within the last 4 weeks of life, however, this limited the potential to explore the impact of palliative care on late chemotherapy. Studies that have established an association between palliative care team involvement and lower rates of chemotherapy near the end of life have concluded that cessation of chemotherapy is due to palliative care involvement.…”
Section: Discussionmentioning
confidence: 93%
“…This qualitative approach to characterize processes involved in medical decision-making based on a medical record review has been used previously. 17 …”
Section: Methodsmentioning
confidence: 99%
“…A ggressive end-of-life (EOL) care is prevalent for persons with advanced cancer. 1 In a recent study of patients with stage IV lung and colorectal cancer, 22% received chemotherapy in the last month of life despite knowing that treatment was unlikely to cure them. 2 Aggressive treatment at the EOL is also associated with poorer quality of life.…”
mentioning
confidence: 99%